AIDS-Related Mycoses: Current Progress in the Field and Future Priorities. Issue 6 (June 2017) - Armstrong-James, Darius; Bicanic, Tihana; Brown, Gordon D.; Hoving, Jennifer C.; Meintjes, Graeme; Nielsen, Kirsten
Abstract : Opportunistic fungal infections continue to take an unacceptably heavy toll on the most disadvantaged living with HIV-AIDS, and are a major driver for HIV-related deaths. At the second EMBO Workshop on AIDS-Related Mycoses, clinicians and scientists from around the world reported current progress and key priorities for improving outcomes from HIV-related mycoses.